Effect of Petroleum Diesel and Biodiesel Spills on Turfgrass. Issue 1 (3rd January 2014) - Johnson, Donald M.; Edgar, Don W.; Karcher, Douglas E.; Richardson, Michael D.; McCalla, John H.
Abstract : This study compared simulated spills of three fuel types at two temperatures on turf damage and recovery. Field research was initiated in Fayetteville, AR on 8 June 2012. Experimental design was a randomized complete block design with four replications. Factors included fuel type, application temperature, and turfgrass surface. Fuel types were petroleum diesel (PD), a 20% biodiesel and 80% petroleum diesel blend (B20), and 100% biodiesel (B100) applied at 32°C and at 74°C. Turfgrass surfaces included creeping bentgrass ( Agrostis stolonifera L. 'SR1020') and bermudagrass ( Cynodon dactylon var. dactylon 'Tifeagle') putting greens and creeping bentgrass ('SR1020'), bermudagrass ('Tifsport'), and zoysiagrass ( Zoysia japonica Steud. 'Meyer') fairways. For Trial 1, 20 mL was applied at the center of each 929‐cm 2 plot on 8 June 2012, and data collection extended through 20 July 2012 (42 days). For Trial 2, 10 mL was applied at the center of each 929‐cm 2 plot on 20 July 2012, and data collection extended through 31 Aug. 2012 (42 days). In 8 of 10 comparisons, there was a statistically significant fuel type‐by‐week‐after‐application interaction, with PD applications resulting in greater damage and slower recovery and B100 resulting in less damage and more rapid recovery. B20 was generally intermediate to PD and B100.